Design of a standalone micro-grid using solar energy - Wong, Anthony Chee Wai (2015)
The global warming issue has led in an international effort in developing clean and renewable energy technologies. These renewable energies are generated by natural resources such as bio-fuel, wind, tidal, geothermal, hydro and solar. However, out of all these natural resources, only solar energy are more accessible to Singapore due to her geographical location. Singapore being located near the equator, the amount of solar radiation received is much higher and consistent all-round the year as compared to other temperate countries. Hence, solar energy will be a promising source of alternative renewable energy in the area of electricity generation. The aim of this project is to design a standalone micro-grid using solar energy for a typical HDB household in Singapore.